2021
DOI: 10.5867/medwave.2021.06.8231
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality in patients hospitalized with COVID-19: A prospective cohort in a Peruvian national referral hospital

Abstract: Objectives To describe and assess clinical characteristics and factors associated with mortality in adult patients with COVID-19 admitted to a national referral hospital in Peru. Methods We conducted a prospective cohort study that included hospitalized patients older than 18 years with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection diagnosis. Patients with a positive rapid serological test on admission but no respiratory symptoms nor compatible images were excluded. We collected the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
6
0
4
Order By: Relevance
“…(5) A preliminary report of a study carried out in a reference hospital in Peru showed an association between the presence of stroke and mortality in patients admitted for COVID-19 (RR = 1.49). They concluded that the presence of stroke is a poor prognostic factor in patients with COVID-19 (26). Previous studies conducted in Peru before the pandemic, reported a rate of 42-68% of patients with independence (mRS0-1) after thrombolysis.…”
Section: Discussionmentioning
confidence: 94%
“…(5) A preliminary report of a study carried out in a reference hospital in Peru showed an association between the presence of stroke and mortality in patients admitted for COVID-19 (RR = 1.49). They concluded that the presence of stroke is a poor prognostic factor in patients with COVID-19 (26). Previous studies conducted in Peru before the pandemic, reported a rate of 42-68% of patients with independence (mRS0-1) after thrombolysis.…”
Section: Discussionmentioning
confidence: 94%
“…hallaron que la mortalidad se vio asociada a la edad (pacientes mayores a 60 años), a los marcadores inflamatorios y al compromiso pulmonar. 35 Sin embargo, en nuestro análisis no encontramos factores riesgo asociados a mortalidad, pensamos que posiblemente esto sea causa del rango etario de los pacientes ingresados previamente discutido, sin dejar de lado al escaso tamaño de la cohorte analizada.…”
Section: Discussionunclassified
“…In the Peruvian population, an association was found with CRP, LDH> 350 UI/L, ferritin> 750 ng/mL, and leukocyte. In addition to D-dimer (> = 1 μg/mL), severe lymphopenia, both in crude and adjusted analyses [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%